A122 THE INFLUENCE OF SEX AND THE GUT MICROBIOTA ON VISCERAL PAIN SENSITIVITY IN MICE. (26th February 2020) - Pujo, J; De Palma, G; Lu, J; Collins, S M; Bercik, P
Abstract: Background: Abdominal pain is a common complaint in patients with chronic gastrointestinal disorders. Its treatment is of limited efficacy as the pathophysiology is largely unknown. Accumulating evidence suggests that gut microbiota is an important determinant of gut function, including visceral sensitivity. Germ-free (GF) mice have been shown to have altered pain signaling, which normalizes after colonization. Sex also appears to play a key role in visceral sensitivity, as abdominal pain is diagnosed predominantly in female patients. Thus, both gut bacteria and sex are important in the regulation of gut nociception, but the underlying mechanisms remain poorly understood. Aims: To investigate the role of gut microbiota and sex in abdominal pain. Methods: We used primary cultures of sensory neurons from dorsal root ganglia (DRG) of female and male conventional mice (SPF) or germ-free (GF) mice, age 7–18 weeks. To study the visceral afferent activity in vitro, calcium mobilization in DRG sensory neurons was measured by inverted fluorescence microscope using a fluorescent calcium probe Fluo-4 (1mM). Two parameters were considered: i) percentage of responding neurons and ii) intensity of neuronal response. First, DRG sensory neurons were stimulated by a TRPV1 agonist capsaicin (12.5nM, 125nM and 1.25µM) or by an agonist mix of G-protein coupled receptors (GPCR: bradykinin, histamine and serotonin; 1µM, 10µM and 100µM). We next cultured Escherichia coli JM83 ( E. coli ) and Enterobacter aerogenes ( E. aer ) overnight in LB and LDMIIG medium, respectively. Bacterial supernatant of 10 10 CFU/mL was diluted to 1% in Krebs Ringer solution to treat DRG neurons from GF/SPF mice and calcium mobilization was measured. Results: The percentage of neurons responding to capsaicin and GPCR agonist was similar in SPF male and SPF female. In contrast, the intensity of the neuronal response was higher in SPF male compared to SPF female mice in response to capsaicin (125nM p<0.035 and 1.25µM p<0.038) but not in response to GPCR. The same trend was observed in GF mice. Neuronal activation induced by capsaicin or GPCR agonist was similar in SPF and GF mice. While bacterial supernatant from E. coli did not affect the activity of sensory neurons, the bacterial supernatant from E. aer induced changes in calcium mobilization in DRG neurons. Conclusions: Our data suggest that at the level of DRG neurons from healthy mice, female sex and the absence of gut microbiota do not predispose to visceral hypersensitivity. In fact, the intensity of neuronal responses to capsaicin appear to be higher in DRGs from male mice. Furthermore, we show that metabolites from certain bacteria can activate sensory neurons. Thus, further studies are needed to investigate the role of gut microbiota and sex in visceral sensitivity Funding Agencies: CIHR